High fecal carriage of bla CTX-M, bla CMY-2, and plasmid-mediated quinolone resistance genes among healthy Korean people in a metagenomic analysis - Jieun Kim (Nature Portfolio, 2021)
Abstract To characterize the carriage of antibiotic resistance genes (ARGs) in the gut microbiome of healthy individuals. Fecal carriage of ARGs was investigated in 61 healthy individuals aged 30 to 59 years through whole metagenome sequencing of the gut microbiome and a targeted metagenomic approach. The number of ARGs in the gut microbiome was counted and normalized per million predicted genes (GPM). In the Korean population, the resistome ranged from 49.7 to 292.5 GPM (median 89.7). Based on the abundance of ARGs, the subjects were categorised into high (> 120 GPM), middle (60‒120 GPM), and low (< 60 GPM) ARG groups. Individuals in the high ARG group tended to visit hospitals more often (P = 0.065), particularly for upper respiratory tract infections (P = 0.066), and carried more bla CTX-M (P = 0.008). The targeted metagenome approach for bla and plasmid-mediated quinolone resistance (PMQR) genes revealed a high fecal carriage rate; 23% or 13.1% of the subjects carried bla CTX-M or bla CMY-2, respectively. Regarding PMQR genes, 59% of the subjects carried PMQR, and 83% of them harboured 2‒4 PMQR genes (qnrB 44.3%, qnrS 47.5% etc.). The presence of bla CTX-M correlated with ARG abundance in the gut resistome, whereas PMQR genes were irrelevant to other ARGs (P = 0.176). Fecal carriage of bla CTX-M and PMQR genes was broad and multiplexed among healthy individuals.